Mode I and mode II delamination of a chopped strand mat E-glass reinforced vinyl ester composite. (21st October 2018) - Johar, M.; Low, K. O.; Israr, H. A.; Wong, K. J.
ABSTRACT: The objective of the present work is to investigate mode I and mode II delamination behaviour of chopped strand mat (CSM) E-glass reinforced vinyl ester (VE) composite. Double cantilever beam and end notched flexure tests were carried out to evaluate the mode I and mode II delamination, respectively. The fracture toughnesses were calculated using the experimental calibration method. Results showed that the average mode I and mode II fracture toughnesses were 185 and 2386 N m −1, respectively. Furthermore, the mode II–mode I ratio for this material was 12.9. This value was the highest when compared with other composite materials from the literature. Finally, through scanning electron micrographs, the dominant failure mechanisms were found to be matrix cracking, fibre debonding and fibre breakage. In addition, shear cusps were observed in mode II specimen, which signified the shearing between the layers.